AKTIVITAS ANTIOKSIDAN DAN BAKTERI ASAM LAKTAT KIMCHI PAKCOY AKIBAT KONSENTRASI GARAM DAN LAMA FERMENTASI - Khasbullah, Fizzaria Khasbullah; Windu Mangiring; Krisnarini; Nurleni Kurniawati (BPFP Faperta UNIB, 2024)
Kimchi is a functional dish made of vegetable that can be made by spontaneous fermentation. Kimchi is a representative traditional fermented and ethnic dish in Korea that has been reported as a healthy food. Commonly, its raw material is Napa cabbage but nowadays its raw material can be from various vegetables, one of them is pakcoy. Among mustard greens, Napa cabbage and pakcoy, pakcoy contains the lowest Carotenoid while Napa cabbage (Brassica Juncea L.) contains the lowest Carotenoid. This research aimed to find out the activity of Lactic Acid Bacteria (LAB) and the antioxidant in pakcoy kimchi caused by salt concentration and fermentation duration. Experimental design by two factors, the first factor (S) was concentration of salt (2%, 4%, and 6%) and the second factor (F) was fermentation duration (2 days, 4 days, and 6 days) with three repetitions. The data was presented in form of diagram then, the result was discussed descriptively. Kimchi was made by mixing supporting material and salt smeared on pakcoy, kept in glass jar and subsequently fermented. The observation was done by LAB activity test with Total Plate Count (TPC) method and antioxidant activity by Diphenyl picrylhydrazin (DPPH) method. The research finding showed that concentration of salt and fermentation duration affected the total of LAB and antioxidant activity. The increase of salt concentration caused the decrease of LAB total, while the increase of fermentation duration caused the increase of LAB total. The increase of salt concentration and fermentation duration caused the decrease of antioxidant activity. The highest antioxidant activity was 86.35%, while the highest LAB content was 4.4x1011CFU/mL.